2023
DOI: 10.3991/ijet.v18i11.41083
|View full text |Cite
|
Sign up to set email alerts
|

Student Online Learning Behavior Characteristics Based on Multidimensional Cognitive Model

Abstract: Analysis of student learning behavior characteristics is an important means for educators to better understand students and improve the quality and effectiveness of teaching in the field of education. It is necessary to refer to students' cognitive levels for analysis of student learning behavior characteristics. However, existing algorithms only focus on the overall performance and grades of students, ignoring the individual differences in learning cognitive levels among students, which affects the accuracy o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…It is important to highlight that the results obtained in the validation of the didactic model can have a positive impact on the curricula of academic programs [30], as areas for improvement in the process of understanding academic texts are identified [31], In this way, tools are provided to students to improve their academic performance and their future professional development.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to highlight that the results obtained in the validation of the didactic model can have a positive impact on the curricula of academic programs [30], as areas for improvement in the process of understanding academic texts are identified [31], In this way, tools are provided to students to improve their academic performance and their future professional development.…”
Section: Discussionmentioning
confidence: 99%
“…According to Artino [10], students appreciate the convenience of online learning; however, given the choice, learners would prefer traditional face-to-face learning over online learning. Therefore, Zhang [11] emphasized the significance of investigating student learning behavior during online learning. Paechter and Maier [12] also found that students preferred face-to-face learning over online forms of learning because of communication purposes and the construction of conceptual knowledge or skills in the application of acquired knowledge.…”
Section: Learning During Covid-19mentioning
confidence: 99%